An Analysis Conflict in “The lady in the looking glass” By Virginia Woolf - Tias Siswanti (AL LUGHAH, 2020)
This research analyzes the conflict that happened on the character in "The lady in the looking glass” this short story by Virginia Woolf was published in 1929. The conflict that happened is Internal and external conflict. This research aims to analyze the conflict in Mrs. Isabella. In real-life conflict always happened, The theory based on Muller and John A William (1982:44) where there is divided conflict into two kinds, first is internal conflict dan second is an external conflict.  This paper tries to make a study from a new perspective and new interpreting this modern short story with the theory of the conflict in the short story. This study aims to know the conflict that happens on Mrs. Isabella as the main character in the short story “The lady in the looking glass”. This study analyzes the sentence and quotation in a short story. The goal of this study is the researcher applied theory about the conflict to Mrs. Isabella has a conflict in the form like mental, physical, and moral.by the character.